Reminders of him [videorecording (Blu-Ray)] - Howe, Tom, 1977- (Universal, 2026)
"A transformative film about motherhood, forgiveness and the power of love to overcome the worst mistake. Desperate to rebuild her life with a daughter she has never known, Kenna finds unexpected compassion in a secret romance with local bar owner Ledger. As dangers develop for both of them, Kenna hopes to find a second chance amid unbearable heartbreak."--